Credit & banking developments in 1960 - Central Bank of Egypt (Cairo : Control of Bank Department, 1960)
The broad objective of the Economic and Social Development plan which started at the beginning of July 1960 is to double the national income in ten years.
osc 14/05/2018
Loans
Keywords: Central Banking; Cairo